2022
DOI: 10.1038/s41598-022-20511-1
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors and healthy lifestyle behaviours among Malaysian adults: National Health and Morbidity Survey 2019

Abstract: This study aimed to investigate the association between socio-demographic factors and designated healthy lifestyle behaviours in a nationally-representative sample of Malaysian adults aged 18 years and above. Secondary data involving 7388 participants aged 18–96 years from the National Health and Morbidity Survey 2019, a national cross-sectional survey, was used in this study. A healthy lifestyle score (0–5 points) was calculated based on five modifiable lifestyle factors: non-smoker, body mass index < 25 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…16 In addition, a study reported pronounced differences in healthy lifestyle behaviors between Malaysian adults based on ethnicity, where Chinese and Other ethnicities were more likely to adopt healthy lifestyles as compared to Malays. 6 The presence of comorbidities and unhealthy lifestyles has been known to increase the likelihood of frailty. 17,18 Various socio-economic indicators have been reported to be associated with frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In addition, a study reported pronounced differences in healthy lifestyle behaviors between Malaysian adults based on ethnicity, where Chinese and Other ethnicities were more likely to adopt healthy lifestyles as compared to Malays. 6 The presence of comorbidities and unhealthy lifestyles has been known to increase the likelihood of frailty. 17,18 Various socio-economic indicators have been reported to be associated with frailty.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the pathological process that contributes to frailty may manifest earlier in life even before old age 5 and frailty was also identifiable among middle-aged and younger populations. 6 Frailty in middle-aged groups was reportedly associated with a greater than two times heightened risk of death, as compared to nonfrail. 7 Given that frailty is dynamic in nature, 8 early detection of people at risk enables the implementation of preventive and intervention actions that may potentially reverse the status of frailty, or prevent the development of frailty.…”
Section: Introductionmentioning
confidence: 98%